Pengembangan Instrumen Tes untuk Mengukur Kemampuan Numerasi Siswa Kelas V Sekolah Dasar - Mida Astarina (Jurnal Kualita Pendidikan, 2022)
The purpose of writing this article is to develop a numeration-based test instrument that is tested for validity, reliability, and the level of difficulty and discriminating power of questions to determine students' numeracy abilities. The subjects of the research trial were fifth grade students of SD Negeri 02 Jolotigo, Talun District, Pekalongan Regency. The validity test was carried out with content validity, criteria, and expert validation. Reliability test is done by looking for the price of the reliability coefficient r. The characteristic test is carried out by determining the level of difficulty and distinguishing power. The results of the reliability test obtained are the value of r in the 0.869 test. The results of the validity test showed that the instrument was declared to meet content validity, criteria, and expert validation with valid criteria. The characteristics of the evaluation instrument developed indicate that the instrument has a proportion of difficulty levels, namely 10% easy questions, 80% moderate questions, and 10% difficult questions. The results of the discriminatory analysis were then combined with the level of difficulty and obtained 10 items of good quality that could be used.